Precision immunotherapy with CAR-T cells in pediatric B-cell acute lymphoblastic leukemia: advances and unanswered challenges - Li, Fu; Zheng, Libo (Frontiers in Oncology, 2026)
Chimeric antigen receptor (CAR) T-cell therapy has emerged as a groundbreaking treatment for pediatric B-cell acute lymphoblastic leukemia (B-ALL), especially for patients with relapsed or refractory disease. CD19-targeted CAR T cells, such as tisagenlecleucel, have demonstrated high rates of complete remission and long-lasting responses in clinical trials. However, challenges such as cytokine release syndrome (CRS), immune effector cell-associated neurotoxicity syndrome (ICANS), antigen escape, and T-cell exhaustion hinder its broader clinical application. Recent advances aim to overcome these obstacles by using multi-targeted CAR-T constructs (e.g., CD19/CD22), creating armored CAR-T cells with enhanced cytokine signaling, and developing optimized combination therapies. Next-generation approaches, including universal CAR-T cells and microenvironment-responsive designs, show promise in improving efficacy and safety. Despite these innovations, further research is needed to refine manufacturing processes, reduce costs, and improve long-term outcomes. This review emphasizes the transformative potential of CAR-T therapy for pediatric B-ALL and discusses critical challenges and future directions in the field.